2013
DOI: 10.1111/1365-2745.12032
|View full text |Cite
|
Sign up to set email alerts
|

Independent variations of plant and soil mixtures reveal soil feedback effects on plant community overyielding

Abstract: Summary 1.Recent studies have shown that the positive relationship between plant diversity and plant biomass ('overyielding') can be explained by soil pathogens depressing productivity more in low than in high diverse plant communities. However, tests of such soil effects in field studies were constrained by experimental limitations to manipulate soil community composition independent of plant community composition. Here, we report of an experiment where feedback effects to plants were tested for both plant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
175
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(197 citation statements)
references
References 47 publications
20
175
2
Order By: Relevance
“…These patterns of host specificity are consistent with results of plant-soil feedback studies that have shown reduced plant growth on soil with a history of plants of the same species or functional group compared to the average community soil (e.g. Cortois et al 2016;Hendriks et al 2013;Mangan et al 2010;Petermann et al 2008). It is, however, crucial to reveal the (fungal) actors and their functional role in grassland plant communities, if we want to increase our understanding of the myriad of plantfungal interactions belowground.…”
Section: Host Specificitysupporting
confidence: 80%
“…These patterns of host specificity are consistent with results of plant-soil feedback studies that have shown reduced plant growth on soil with a history of plants of the same species or functional group compared to the average community soil (e.g. Cortois et al 2016;Hendriks et al 2013;Mangan et al 2010;Petermann et al 2008). It is, however, crucial to reveal the (fungal) actors and their functional role in grassland plant communities, if we want to increase our understanding of the myriad of plantfungal interactions belowground.…”
Section: Host Specificitysupporting
confidence: 80%
“…These results indicate that high plant species diversity ameliorated the inhibitory effects of soil biota that were expressed at low diversity and provide a direct test of the negative effects of soil biota on plants growing at reasonably natural, but low richness levels. Since our low-diversity plots had between 2 and 5 species, our results are quite conservative relative to other tests comparing feedback effects in high-diversity soil to soil collected from monocultures of species (e.g., Petermann et al 2008;Hendriks et al 2013). Our results suggest that local patches of plants that contain only a few species (which are likely to be more common in nature than the monocultures that are more commonly experimented with in this context) can accumulate inhibitory soil biota to a greater extent than higher diversity patches.…”
Section: Discussionmentioning
confidence: 85%
“…Concomitantly, plant productivity increased nearly 500 % at high versus low diversity, primarily because of the strong suppressive effects of density-dependent disease on plant productivity at low diversity (see also Knops et al 1999). Hendriks et al (2013) found that soil feedbacks in soil in which species in monoculture were grown were substantially more negative than feedbacks in soil containing diverse mixture of the same species grown in monocultures. Taken together, these results suggest that the accumulation of inhibitory soil biota at low plant species diversity may help to explain the common pattern of low species diversity corresponding with low ecosystem productivity (Cardinale et al 2007;Eisenhauer et al 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the observed alterations in plant community composition will also affect soil community composition, as each plant species creates its own soil biotic community (Bezemer et al 2010). Via biotic plant-soil interactions, these species-specific soil communities can differentially affect the growth of subsequent plant species growing in that soil, which could then alter the succession of the community as a whole (van de Voorde et al 2011, Hendriks et al 2013. Even when the direct effects of biochar addition disappear rapidly in the following growing seasons, for example, due to leaching or utilization of mobile ions such as K, the effect of biochar addition will remain visible in the plant community and in the ecosystem via altered mechanisms like seed production, competition, and plant-soil interactions over a much longer period.…”
Section: Long-term Cascading Effects Of Biocharmentioning
confidence: 99%